A proposta hegeliana de organizac?a?o poli?tica a partir da cri?tica ao Estado como “propriedade privada” - Tidre, Polyana (Revista Eletrônica Estudos Hegelianos, 2018)
The article aims to examine the relationship between Hegel's conception of political organization and his critique against the State understood as ‘private property’. My research is based on the ideas introduced by Hegel in The Elements of the Philosophy of Right, of 1820, and On the English Reform Bill, published shortly before his death. After taking into account the historical-political particularities of the time by contextualizing the claims for modernization and reforms proposed by Hegel – source of controversy between the scholars – I will, then, investigate Hegel's critique of an instrumentalization of the State in favor of particular interests, emphasizing how, according to Hegel, the danger is in the subordination of the State affairs to the birth or money-related privileges, as well as to a ‘general will’ of the people, as long as ‘the people’ means a ‘formless mass’ who ‘does not know what it wants’. Beyond the critique, Hegel also offers his own conception of political organization, which I examine in the last part of the article. In doing so I will take a closer look specially at the role that, according to Hegel, following in Plato's footsteps, bureaucracy must play in this effort to protect the State. However, instead of conceiving a State directed exclusively by experts, Hegel also endorses a representative system, formed by social-professional groups, integrating the Sta?nde, as a conditioning factor in the process of participation of the people in the State, which I subsequently analyze. I offer my interpretation of Hegel's position towards a frequently misunderstood democracy and I show how Hegel, linking work, through the Sta?nde, to the political sphere, contributes to the promotion of a more democratic conception of State.